2021
DOI: 10.1002/mco2.97
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitors: A potential therapeutic approach for triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) cells lack expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor‐2 (HER‐2). Thus, TNBC does not respond to hormone‐based therapy. TNBC is also an aggressive subtype associated with poorer prognoses compared to other breast cancers. Conventional chemotherapeutics are used to manage TNBC although systemic relapse is common with limited benefits being reported as well as adverse events being documented. Here, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 142 publications
0
14
0
Order By: Relevance
“…CMGCs and AGC are known to regulate a variety of cell metabolism, growth, proliferation, survival, and anti-apoptosis activities and extensively participate in the control of cell fate decisions; thus, they have been of interest in cancer research. In breast cancer, inhibition of CDK4/6 using small-molecule inhibitors such as palbociclib, abemacilib, and ribociclib has shown substantial promise in early-stage clinical studies, which induce tumor stabilization and increase the rates of tumor shrinkage 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…CMGCs and AGC are known to regulate a variety of cell metabolism, growth, proliferation, survival, and anti-apoptosis activities and extensively participate in the control of cell fate decisions; thus, they have been of interest in cancer research. In breast cancer, inhibition of CDK4/6 using small-molecule inhibitors such as palbociclib, abemacilib, and ribociclib has shown substantial promise in early-stage clinical studies, which induce tumor stabilization and increase the rates of tumor shrinkage 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are three FDA‐approved CDK4/6 inhibitors: palbociclib, ribociclib, and abemaciclib which are used in the treatment of ER+/HER2– advanced BC. In TNBC, Rb dysfunction has been evident in approximately 30% of patients, which makes CDK4/6 inhibitors a promising therapeutic option (Hu et al, 2021; Saleh et al, 2021). Several clinical trials are investigating the use of CDK4/6 inhibitors in conjunction with other agents in TNBC.…”
Section: Treatmentmentioning
confidence: 99%
“…The first-generation inhibitors, such as flavopiridol, roscovitine, UNC-01, etc., due to the lack of selectivity for different types of CDK and serious side effects in the clinical, their development was stopped (97,98). On the contrary, the second generation of CDK inhibitors show better anti-tumor activity and selectivity, especially those targeting CDK4/6, like palbociclib, ribociclib, abemaciclib, etc., which can inhibit RB phosphorylation and block the cell cycle in G1 phase, preventing the proliferation of breast cancer (99,100). Clinical trials have shown that it has good efficacy in the treatment of metastatic breast cancer with HR+ and HER2when combined with endocrine therapy (101).…”
Section: Cdk Inhibitorsmentioning
confidence: 99%